PSIX-1 Fecal microbiome of dairy calves fed with fresh or frozen maternal colostrum or colostrum powder - Virgínio Júnior, Gercino F (J Anim Sci, 2020)
Besides the importance for passive immune transfer, the supply of colostrum accelerates the bacterial colonization of the calf small intestine by providing nutrients, that will function as bacteria growth substrate, as well being a microorganism inoculum source. However, it is not known whether the effect is maintained when the calves are fed with frozen colostrum or colostrum powder. The present work evaluated 15 Holstein calves housed in tropical shelters, fed one of the colostrum sources: I – fresh colostrum from the dam (n = 5), II – frozen colostrum and III – colostrum powder, a dose of 150g of IgG (n = 5). Animals fed with fresh or frozen colostrum received a corresponding volume 10% of its birth weight of high-quality colostrum (IgG > 50g / L). All animals were fed within 4h after birth. From the second meal, calves received 6 L of liquid diet, divided into two meals, being weaned at the 8(th) week of age. After weaning, calves were grouped housed, and fed with starter and coast-cross hay ad libitum. To evaluate the microbiome, fecal samples were collected at birth and at weeks 1, 2, 4, 8 and 10. The microbial community was determined by sequencing V3 and V4 region amplicons of the 16S rRNA gene that was amplified by PCR and sequenced by the Illumina MiSeq platform. There was no treatment effect for the diversity indices, evenness and richness. Simpson’s diversity and evenness had no effect for weeks. Weeks 1 and 2 had less Shannon’ diversity. Richness was higher for week 0. Analyzing the relative abundance, 31 phyla were identified in the fecal samples, the most abundant being Bacteriodota, Firmicutes_A, Proteobacterias, Fusobacteriota and Firmicutes. Different sources of colostrum can be used to feed dairy calves, without affecting the diversity in the colonization of the intestinal tract.